Development of Student Worksheet with an Ethnoscience Approach to Wati Plants Through Liveworksheet Applications - Nia Sahnia Rumadan; Henie Poerwandar Asmaningrum; Novike Bela Sumanik (IJCER (International Journal of Chemistry Education Research), 2023)
This study aims to develop the student worksheet on Addictive Substances material with the Wati Plant ethnoscience approach through the Liveworksheet application that is feasible in terms of validity and practicality. This type of research is R&D research using the ADDIE model, namely: Analyze,  Design, Development, Implementation, and Evaluation. However, this research is limited to the third stage, namely the Development stage. The research subjects were one material expert, one media expert, one practitioner, and ten students of the  Chemistry Education Department, Musamus University. The instruments used in data collection were interview guidelines and questionnaires. The results showed that the student worksheet on Addictive Substances material with the Wati Plant ethnoscience approach through the Liveworksheet application got a percentage of 94% at the 6th meeting and 97% at the 7th meeting from material experts, 95% at meetings 6 and 7 from media experts, 84% at the 6th meeting and 86% at the 7th meeting of practitioner responses and 90% at the 6th meeting and 88% at the 7th meeting of student responses. Based on the results of these studies, it can be concluded that the student worksheet on Addictive Substances material with the Wati Plant ethnoscience approach through the Liveworksheet application is feasible in terms of validity and practicality aspects